2015
DOI: 10.4236/fns.2015.62021
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Minerals from Food Supplements in a German Population—A Nationwide Survey

Abstract: Introduction: Studies indicate that 17.9% -60% of adults in Germany and Europe regularly use food supplements. Some reports suggest that their use might be responsible for excessive nutrient intake. The purpose of this survey was to examine the quantitative mineral intakes from food supplements: whether the tolerable upper intake levels (ULs) with supplements alone, or in combination with food was exceeded was checked. Methods: The survey was carried out by the Association for Consumer Research, Nürnberg, Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…A consumer survey recently conducted in Germany showed that just 2.5% of the questioned participants were actually taking manganese supplements (value recalculated; among all supplement users, the proportion of those taking manganese supplements amounted to 15%). Nevertheless, 14% of them almost reached the upper “Adequate Intake” (AI) already with the supplement source (4 mg per day at P95) . This finding underlines that manganese supplements do not play a major role for the general population, but might lead to high intakes by certain food supplement consumers.…”
Section: Estimates Of the Dietary Manganese Exposure In The Adult Popmentioning
confidence: 89%
“…A consumer survey recently conducted in Germany showed that just 2.5% of the questioned participants were actually taking manganese supplements (value recalculated; among all supplement users, the proportion of those taking manganese supplements amounted to 15%). Nevertheless, 14% of them almost reached the upper “Adequate Intake” (AI) already with the supplement source (4 mg per day at P95) . This finding underlines that manganese supplements do not play a major role for the general population, but might lead to high intakes by certain food supplement consumers.…”
Section: Estimates Of the Dietary Manganese Exposure In The Adult Popmentioning
confidence: 89%
“…According to a current representative study, 16.2% of the German population are supplementing their mineral intake, and 23% of this group of people are including products containing Se in the form of capsules, tablets, pills and other similar forms. Thus, about 4% of the German consumers are using Se-containing food supplements [ 49 ]. Brazil nuts are known for their high natural Se content, but are not a commonly-eaten food in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the need for selenium is largely covered by animal produce, such as meat or fish. The biofortification of plant produce allows for vegetarians or vegans in particular to fulfill their needs naturally and as an alternative to food supplements [12,13]. A previous consumer survey clearly indicated that German consumers would prefer selenium-rich apples instead of food supplements for improving their selenium supply [14].…”
Section: Introductionmentioning
confidence: 99%